'20 days protected learning' - students' experiences of an overseas nurses programme - 4 years on: a retrospective survey - Brown Petra; Jordan Gill (BMC, 2011)
Abstract Background From September 2005 the Nursing and Midwifery Council (NMC) introduced new arrangements for the registration of non-EU overseas nurses which requires all applicants to undertake '20 days of protected learning' time in the UK and for some, a period of supervised practice. A survey was undertaken at Bournemouth University, which offers a '20 days protected learning only' programme, to elicit overseas nurses' demographic details, experiences in completing the programme and their 'final destinations' once registered. Methods An online survey was devised which contained a mixture of tick box and open ended questions which covered demographic details, views on the programme and final destinations This was uploaded to http://www.surveymonkey.com/ and sent out to nurses who had completed the Overseas Nurses Programme (ONP) with Bournemouth University (n = 1050). Quantitative data were analysed using descriptive statistics and the qualitative data were coded and analysed using content analysis. Results There were 251 respondents (27.7% response rate). The typical 'profile' of a nurse who responded to the survey was female, aged 25-40 years and had been qualified for more than 5 years with a bachelors degree. The majority came from Australia on a 2 year working holiday visa and the key final destination in the UK, on registration with the NMC, was working for an agency. There were five key findings regarding experience of the programme. Of those surveyed 61.2% did not feel it necessary to undergo an ONP; 71.6% felt that they should be able to complete the programme on-line in their own country; 64.2% that the ONP should only contain information about delivery of healthcare in UK and Legal and professional (NMC) issues; 57% that European nurses should also undergo the same programme and sit an IELTS test; and 68.2% that the programme was too theory orientated; and should have links to practice (21%). Conclusions The NMC set the admissions criteria for entry to the register and Standards for an ONP. The findings of this survey raise issues regarding the perceived value and use of this approach for overseas nurses, and it may be helpful to take this into account when considering future policy.